The involvement of ADAR1 in chronic unpredictable stress-induced cognitive impairment by targeting DARPP-32 with miR-874-3p in BALB/c mice - Wang, Yanfang; Liu, Yingxin; Zhao, Ziwei; Wu, Xinyu; Lin, Jiabin; Li, Yufei; Yan, Wei; Wu, Yi; Shi, Yanfei; Wu, Xindi; Xue, Ying; He, Jiaqian; et al. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Chronic stress exposure is the main environmental factor leading to cognitive impairment, but the detailed molecular mechanism is still unclear. Adenosine Deaminase acting on double-stranded RNA1(ADAR1) is involved in the occurrence of chronic stress-induced cognitive impairment. In addition, dopamine and Adenosine 3′5′-monophosphate-regulated phospho-protein (DARPP-32) gene variation affects cognitive function. Therefore, we hypothesized that ADAR1 plays a key role in chronic stress-induced cognitive impairment by acting on DARPP-32. Methods: In this study, postnatal 21-day-old male BALB/c mice were exposed to chronic unpredictable stressors. After that, the mice were treated with ADAR1 inducer/inhibitor. The cognitive ability and cerebral DARPP-32 protein expression of BALB/c mice were evaluated. In order to explore the link between ADAR1 and DARPP-32, the effects of ADAR1 high/low expression on DARPP-32 protein expression in vitro were detected. Results: ADAR1 inducer alleviates cognitive impairment and recovers decreased DARPP-32 protein expression of the hippocampus and prefrontal cortex in BALB/c mice with chronic unpredictable stress exposure. In vivo and in vitro studies confirm the results predicted by bio-informatics; that is, ADAR1 affects DARPP-32 expression via miR-874-3p. Discussion: The results in this study demonstrate that ADAR1 affects the expression of DARPP-32 via miR-874-3p, which is involved in the molecular mechanism of pathogenesis in chronic unpredictable stress-induced cognitive impairment. The new findings of this study provide a new therapeutic strategy for the prevention and treatment of stress cognitive impairment from epigenetics.